MORAL EDUCATION: COMPARATIVE ANALISYS OF CHARACTER EDUCATION FRAMEWORK IN INDONESIA AND CHINA - handayani, puspita; Kholis, Nur (Antis-Publisher, 2024)
Indonesia and China are two countries in the Asian region that generally have many similarities in culture, social, and economy. In the concept of education, these two countries carry the concept of character education as a foundation for building and strengthening the nation. This research uses System Literature Review, which is a research method used to identify, evaluate, and interpret the results of certain research, certain topics, or phenomena of concern. It is known that the character education framework developed by Indonesia and China has similarities derived from Top-Down policies, the implementation of Character Education from both countries is focused on education units, the purpose of character education is an effort to improve the morals of citizens, it is hoped that good morals will improve the image of the nation.